2022
DOI: 10.47391/jpma.3793
|View full text |Cite
|
Sign up to set email alerts
|

A case report on Fibular Aplasia, Tibial Campomelia, Oligosyndactyly Syndrome variant in a Male Infant

Abstract: Fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO syndrome) is a rare, genetic, congenital limb malformation characterized by unilateral or bilateral fibular aplasia, tibial campomelia, and lower limb oligosyndactyly involving the lateral rays. A newborn male born at term via a Caesarean Section presented with malformations consisting of tibial campomelia, unilateral fibular hypoplasia, and oligosyndactyly, a “FATCO variant” case. On radiographic examination, an anterolateral shortened and bowed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…FATCO is an uncommon entity whose prevalence has been reported to be less than one per million births ( https://www.orpha.net/consor/cgi-bin/OC_Exp.php?lng=ES&Expert=2,492 ). The majority of reported cases, as with the case reported here, present with the defined criteria for the complex, i.e., Fibular Aplasia, Tibial Campomelia and Oligosyndactyly ( Hecht and Scott, 1981 ; Cuillier et al, 2004 ; Courtens et al, 2005 ; Monteagudo et al, 2006 ; Kitaoka et al, 2009 ; Karaman and Kahveci, 2010 ; Vyskocil et al, 2011 ; Bieganski et al, 2012 ; Ekbote and Danda, 2012 ; Goyal, 2014 ; Sezer et al, 2014 ; Bastaki et al, 2015 ; Hazan et al, 2016 ; Nogueira et al, 2016 ; Smets et al, 2016 ; D’Amato Gutiérrez and Palacio Díaz, 2016 ; Abdalla and El-Beheiry, 2017 ; Ahmad et al, 2017 ; Petricevic, 2017 ; Guevara Zárate et al, 2018 ; Otaryan et al, 2018 ; Isik et al, 2019 ; Önder Yılmaz et al, 2019 ; Igoche and Umaru, 2020 ; Izadi and Salehnia, 2020 ; Kavipurapu et al, 2021 ; Marinho et al, 2021 ; Mishra and Verma, 2021 ; Yucel Celik et al, 2021 ; Mumtaz Hashmi et al, 2022 ; Georgeos and Elgzzar, 2022 ; Georgescu et al, 2022 ), but other systemic manifestations have been described in some cases ( Hecht and Scott, 1981 ; Courtens et al, 2005 ; Kitaoka et al, 2009 ; Bieganski et al, 2012 ; Nogueira et al, 2016 ; Isik et al, 2019 ; Igoche and Umaru, 2020 ; Kavipurapu et al, 2021 ; Marinho et al, 2021 ; Georgeos and Elgzzar, 2022 ). Although data is scarce, no significant difference in laterality nor with the frequency of other extra-skeletal conditions has been found, probably due to the rarity of this entity.…”
Section: Discussionmentioning
confidence: 99%
“…FATCO is an uncommon entity whose prevalence has been reported to be less than one per million births ( https://www.orpha.net/consor/cgi-bin/OC_Exp.php?lng=ES&Expert=2,492 ). The majority of reported cases, as with the case reported here, present with the defined criteria for the complex, i.e., Fibular Aplasia, Tibial Campomelia and Oligosyndactyly ( Hecht and Scott, 1981 ; Cuillier et al, 2004 ; Courtens et al, 2005 ; Monteagudo et al, 2006 ; Kitaoka et al, 2009 ; Karaman and Kahveci, 2010 ; Vyskocil et al, 2011 ; Bieganski et al, 2012 ; Ekbote and Danda, 2012 ; Goyal, 2014 ; Sezer et al, 2014 ; Bastaki et al, 2015 ; Hazan et al, 2016 ; Nogueira et al, 2016 ; Smets et al, 2016 ; D’Amato Gutiérrez and Palacio Díaz, 2016 ; Abdalla and El-Beheiry, 2017 ; Ahmad et al, 2017 ; Petricevic, 2017 ; Guevara Zárate et al, 2018 ; Otaryan et al, 2018 ; Isik et al, 2019 ; Önder Yılmaz et al, 2019 ; Igoche and Umaru, 2020 ; Izadi and Salehnia, 2020 ; Kavipurapu et al, 2021 ; Marinho et al, 2021 ; Mishra and Verma, 2021 ; Yucel Celik et al, 2021 ; Mumtaz Hashmi et al, 2022 ; Georgeos and Elgzzar, 2022 ; Georgescu et al, 2022 ), but other systemic manifestations have been described in some cases ( Hecht and Scott, 1981 ; Courtens et al, 2005 ; Kitaoka et al, 2009 ; Bieganski et al, 2012 ; Nogueira et al, 2016 ; Isik et al, 2019 ; Igoche and Umaru, 2020 ; Kavipurapu et al, 2021 ; Marinho et al, 2021 ; Georgeos and Elgzzar, 2022 ). Although data is scarce, no significant difference in laterality nor with the frequency of other extra-skeletal conditions has been found, probably due to the rarity of this entity.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that research productivity differ in different countries may reveal different countries' capabilities in science and technology. 3,4,6,8,[25][26][27][28] This scientometric analysis showed that more than 50% of documents published by authors from the United States, and nearly 90% of global foot and ankle documents were contributed by the top 10 countries. In addition, most of the top 10 were developed countries.…”
Section: Discussionmentioning
confidence: 99%